Konsep Kependudukan Program KB di Indonesia dan Organisasi KB untuk Kesehatan - Aldino, Vero Hari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The objective of the research is to explain the history of UN in Indonesia, to overcome the factors that influence the development of UN, to explain UN organizations in Indonesia and UN programmes in Indonesia. To explain the concept of family planning. This method of research is a type of descriptive research, which means that this research describes an object, phenomenon, or social setting in the form of writing containing a quotation of data or facts or natural manifestations in the field. The results of the research are from the above description we conclude that the family planning program is an attempt to enhance the care and role as well as society through adult marriage age (PUP), birth arrangement, building family resilience, improving the well-being of small families, happiness and prosperity. The main objective of the National Commission's program is to fulfil the public's orders to provide quality reproductive health services, lower the levels of I.C.I. and I.B. as well as overcome reproductive-health problems in order to build quality small families.